2021
DOI: 10.3390/life11080784
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes as an Emerging Paradigm for Regenerative Therapy and Nano-Medicine: A Comprehensive Review

Abstract: Mesenchymal Stem Cells are potent therapeutic candidates in the field of regenerative medicine, owing to their immunomodulatory and differentiation potential. However, several complications come with their translational application like viability, duration, and degree of expansion, long-term storage, and high maintenance cost. Therefore, drawbacks of cell-based therapy can be overcome by a novel therapeutic modality emerging in translational research and application, i.e., exosomes. These small vesicles derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 173 publications
0
17
0
Order By: Relevance
“…Due to the multiple strengths of adipose tissue, exosomes secreted by adipose-derived stem cells are more applicable to the treatment of the post-tendon injury. Extensive studies have established that ADSC-Exos can be effective in a wide range of diseases, especially cardiac, renal, neurological, and musculoskeletal disorders [ 30 , 81 ]. The aspects of exosomes that play a role in distinct diseases include the following: accelerating skin wound healing, promoting immune system regulation, treating osteoarthritis, etc.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the multiple strengths of adipose tissue, exosomes secreted by adipose-derived stem cells are more applicable to the treatment of the post-tendon injury. Extensive studies have established that ADSC-Exos can be effective in a wide range of diseases, especially cardiac, renal, neurological, and musculoskeletal disorders [ 30 , 81 ]. The aspects of exosomes that play a role in distinct diseases include the following: accelerating skin wound healing, promoting immune system regulation, treating osteoarthritis, etc.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The actions of ADSC-Exos in the healing process of tendon injuries are divided into four main parts: the effects of ADSC-Exos in the healing process of tendon injury are divided into four main components: facilitating angiogenesis, diminishing the inflammatory response, fostering the proliferation and migration of tendon cells, and speeding up collagen synthesis [ 26 , 28 , 30 , 82 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular stem cell types considered for cell therapy include Embryonic Stem Cells, induced Pluripotent Stem Cells, and Adult Multipotent Stem Cells, like Mesenchymal Stem Cells (MSCs). Due to the complex ethical concerns intervening in the use of the former, MSCs and their derivatives are now gaining the spotlight (Panda et al, 2021). MSCs are adult multipotent stem cells that can be derived from various sources for instance Bone Marrow, Wharton's Jelly, Adipose Tissue and Dental pulp (Singh et al, 2017).…”
mentioning
confidence: 99%
“…This can be done by the aid of biotechnological and bioengineering techniques which can, for example, be used to modify their surface markers for a targeted delivery. Additionally, their vesicular membrane bound structure can be utilized for encapsulation of drugs in order to employ them as a drug delivery vehicle (Panda et al, 2021). However this field requires extensive research and an ADME database as suggested by Baek et al (2019), should be established.…”
mentioning
confidence: 99%